Perspectives of non-small cell lung cancer treatment with angiogenesis inhibitors - Szostakiewicz, Barbara; Jassem, Jacek; Dziadziuszko, Rafał (Contemporary Oncology/Współczesna Onkologia, 2003)
Lung cancer is the most common malignancy in Poland. Current treatment outcome in this disease remains unsatisfactory and has not improved despite the development of surgical and anaesthetic techniques and application of combined modality approaches. The multi-stage process of neoangiogenesis contributes to progression of the disease and development of metastases. In experimental tumor models inhibition of this process leads to stabilisation or regression of the disease. The following groups of angiogenesis inhibitors are now being evaluated in preclinical and clinical trials: inhibitors of vascular endothelial growth factor (VEGF), antagonists of VEGF receptors, inhibitors of matrix metalloproteinases, endogenous angiogenesis inhibitors, antagonists of integrins, angiozymes and squalamine. The inhibition of angiogenesis is also exerted by traditional chemotherapeutic drugs. The aim of this article is to provide a brief review of angiogenesis inhibitors, currently under evaluation in numerous clinical trials on non-small cell lung cancer (NSCLC). So far, none of the mentioned drugs has been shown to produce clinical benefit in this tumor. The improvement of the overall survival with antibodies against VEGF recently demonstrated in patients with advanced colon cancer, gives hope for similar advantage in NSCLC. As angiogenesis inhibitors have side effects unusual for conventional cytostatics, special consideration should be given to the design and monitoring of clinical trials using these agents.